(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The implementation of VOQ and Iterative Probabilistic Scheduling with Parallel Processing (IPSWPP) in ns-2 is setup as described. The simulator is configure to model a heterogeneous router processor system having the dispatching processor, multiple worker processor and one transmitting processors. To examine the performance of IPSWPP for processing variable length packets in a realistic system, we conduct the simulation by varying the mean packet size of the incoming packets.